2008
DOI: 10.1593/neo.08602
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Monitoring of Breast Cancer during Neoadjuvant Chemotherapy Using Optical Tomography with Ultrasound Localization

Abstract: The purposes of this study were 1) to investigate the feasibility of using optical tomography in the near-infrared (NIR) spectrum combined with ultrasound (US) localization (NIR/US) in monitoring tumor vascular changes and assessing tumor pathological response during chemotherapy and 2) to compare the accuracy of NIR/US with magnetic resonance imaging (MRI) in predicting residual cancer after neoadjuvant chemotherapy. Eleven female patients were studied during treatments with a combined imager consisting of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
86
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(91 citation statements)
references
References 50 publications
5
86
0
Order By: Relevance
“…An important practical advantage of our DOSI approach is that it can be used frequently in unconventional settings such as a doctor's surgery or clinic. Portable optical imaging platforms can easily supplement existing radiological methods either as standalone devices or as units integrated into established technologies such as ultrasound, mammography or MRI [40,53].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An important practical advantage of our DOSI approach is that it can be used frequently in unconventional settings such as a doctor's surgery or clinic. Portable optical imaging platforms can easily supplement existing radiological methods either as standalone devices or as units integrated into established technologies such as ultrasound, mammography or MRI [40,53].…”
Section: Discussionmentioning
confidence: 99%
“…DOS-measured tumour concentrations of deoxyhaemoglobin (ctHHb), oxyhaemoglobin (ctO 2 Hb) and ctH 2 O dropped 27 ± 15, 33 ± 7 and 11 ± 15 per cent, respectively, within one week of the first treatment for pathology-confirmed responders (N = 6), while non-responders (N = 5) and normal side controls showed no significant changes in these parameters. Later studies have subsequently reported correlations between sensitive NIR parameters and pathological response [39][40][41].…”
Section: (C) Imaging Neoadjuvant Therapy Responsementioning
confidence: 98%
“…DOS tomography measures bulk, or large volume, total tissue hemoglobin aging biologic markers that refl ect tissue function and hence should better predict response to therapy. Diffuse optical spectroscopic (DOS) tomography provides information about the intrinsic vascular and ultrastructural biophysical composition of breast tissue (9)(10)(11)(12)(13)(14)(15)(16)(17). The validation of DOS tomographic images and spectra requires both morphologic diagnoses from histopathologic examination and parametric analysis of tissue features, beyond the declared pathologic diagnosis ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…Monitoring of breast cancer treatment response to neoadjuvant chemotherapy with diffuse optical spectroscopy ( 9 ) or tomography ( 11,12,32,45 ) has demonstrated encouraging initial results in single-trial studies. Zhu and colleagues ( 11 ), who evaluated vessel density changes in 16 subjects in response to neoadjuvant chemotherapy while monitoring them with near-infrared imaging, observed a moderately signifi cant ( P = .056) correlation between the quantitative MVD measures of existing vessels (CD31-positive vessels) in residual tumor specimens and Hb T level, but no statistical significance was found between responder and nonresponder groups.…”
Section: Discussionmentioning
confidence: 99%
“…Chapgar et al [10] noted that, in 189 patients treated with NAC at the MD Anderson Cancer Center (Houston, TX), the correlation of physical examination, mammography and US with pathological tumour size was weak to moderate with correlation coefficients of 0.42, 0.41 and 0.42 respectively. Small case series however, have reported much higher accuracy of US in predicting pCR [11,12] and there is increasing interest in employing advanced ultrasound-based technologies, for example assessing vascularity, to further improve performance [13,14].…”
Section: Patients Electing To Undergo Nac Are Closely Monitored In Mmentioning
confidence: 99%